Telogen effluvium incidence in women wearing hijab compared to non-hijab: A cross-sectional study - Sirait, Sondang Pandjaitan; Widaty, Sandra; Legiawati, Lili; Surachmiati Suseno, Lis; Krisanti, Roro Inge Ade; Budianti, Windy Keumala; Miranda, Eliza; Rihatmadja, Rahadi; Oktarina, Caroline; Pandelaki, Paulus Anung Anindita; Situmeang, Irhen (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Hair loss is a normal experience, but if the amount of hair loss exceeds what is considered normal, it will usually cause anxiety for the patient. In Indonesia, almost every Muslim woman wears a hijab. The hijab is one of many factors believed to cause hair loss. Telogen effluvium (TE) itself is a hair cycle disorder in which the anagen phase terminates prematurely, resulting in diffuse club hair loss without scarring, and TE itself has many risk factors. The purpose of this study was to determine the relationship between the incidence of TE in women who wear hijabs and those who do not. Methods: This cross-sectional study was conducted from August 2019 to April 2021 involving 188 healthy women aged 18 years and over who had not yet reached menopause. In the hijab group, it was determined that they should wear a minimum of 8 hours a day for at least 5 years. The test was carried out on hair that had not been washed using a trichogram, to look for hair characteristics in each group (hijab-wearing and non-hijab-wearing). Analysis of the data obtained was carried out using the Chi-square test and odds ratio. Results: Telogen effluvium was higher in subjects wearing hijab (26.8%) than in subjects who did not wear hijab (18.1%), (p-value 0.040, OR 2.036). Conclusion: There was a significant relationship between TE in women who wear hijab compared to those who do not. Further studies should be conducted in other populations with a larger sample size to confirm these results.